Aplikasi Diagnosa Penyakit Covid-19 Menggunakan Metode Naïve Bayes Berbasis Website - Bogi Anwar Suhandono; Samsoni (CV. Multi Kreasi Media, 2023)
In January 2020, the World Health Organization (WHO) declared the coronavirus outbreak a global health emergency of unknown cause. China identified that this case was caused by a new coronavirus called COVID-19. The Naive Bayes method is a way to deal with data uncertainty with a simple probabilistic classification method based on Bayes' theorem through training data from a number of data efficiently. A method that applies rules related to probability or likelihood values to produce a decision and the right information based on the causes that occur. This application can help doctors and medical staff work in terms of speed and accuracy in diagnosing diseases and their solutions by designing a website-based application that can diagnose COVID-19 early using the PHP programming language and MySQL database. This website uses the naïve Bayes method as a calculation by taking data from the symptoms experienced by the user and the weight value of each symptom for the disease filled in by the expert. This application can help experts in early diagnosing COVID-19 and similar diseases with almost the same symptoms as influenza, dengue fever and the common cold.